Electrical Conductances of Tetrabutylammonium and Decamethylferrocenium Hexafluorophosphate in Organic Solvents - Goldfarb, Darío L.; Longinotti, María Paula; Corti, Horacio Roberto (Springer, 2001)
Fil: Goldfarb, Darío L.. Comisión Nacional de Energía Atómica; Argentina